If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(2z + -6) = 4 + -3z Reorder the terms: 10 + -1(-6 + 2z) = 4 + -3z 10 + (-6 * -1 + 2z * -1) = 4 + -3z 10 + (6 + -2z) = 4 + -3z Combine like terms: 10 + 6 = 16 16 + -2z = 4 + -3z Solving 16 + -2z = 4 + -3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3z' to each side of the equation. 16 + -2z + 3z = 4 + -3z + 3z Combine like terms: -2z + 3z = 1z 16 + 1z = 4 + -3z + 3z Combine like terms: -3z + 3z = 0 16 + 1z = 4 + 0 16 + 1z = 4 Add '-16' to each side of the equation. 16 + -16 + 1z = 4 + -16 Combine like terms: 16 + -16 = 0 0 + 1z = 4 + -16 1z = 4 + -16 Combine like terms: 4 + -16 = -12 1z = -12 Divide each side by '1'. z = -12 Simplifying z = -12
| 6a+3=2a-13 | | 4.4y=-88 | | -6x+56=-9-31 | | 2(-3)=76 | | 9.2y=-88 | | 0.71*x=3 | | 2n+5=(n-2)-n | | 8=2x-3y | | 3(3v-2)=4(2v+2) | | 2X+1-4=-2X-34 | | 4z/10+7=8 | | 12x=2x+10x+1 | | 3m-8m=110 | | x/9+3=6 | | 9(1.082x+1)=15 | | z/7+3=6 | | 15x^2-47x-10=0 | | 137-(6x+5)=6(x+9)+x | | 2/3x–6=9 | | 5x-4=x+3*2 | | 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x | | 15z-2=(2z+3) | | 3x-(12x-x)=5+2(x-1)-1 | | 3y+5y+2y= | | 6r-6=72-6 | | 5n-30=20 | | 3x-(12-x)=5+2(x+1)-1 |